2020
DOI: 10.1038/s41598-020-75131-4
|View full text |Cite
|
Sign up to set email alerts
|

In-situ porosity recognition for laser additive manufacturing of 7075-Al alloy using plasma emission spectroscopy

Abstract: Poor quality and low repeatability of additively manufactured parts are key technological obstacles for the widespread adoption of additive manufacturing (AM). In-situ monitoring and control of the AM process is vital to overcome this problem. This paper describes the combined artificial intelligence and plasma emission spectroscopy to identify the porosity of AM parts during the process. The time- and position-synchronized spectra were collected during the directed energy deposition (DED) manufacturing proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…21 Recently, several methods have been designed for real-time porosity inspection during AM by online monitoring of melt-pool features (e.g., temperature, geometry, and radiation intensity). 2226 Although these methods can examine porosity with a high accuracy, a large amount of iterative testing is required to establish a new relationship between the melt pool features and porosity once the target AM process or material is changed. In addition, the authors proposed a femtosecond laser-based transient thermoreflectance (TTR) measurement system for in situ porosity inspection.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, several methods have been designed for real-time porosity inspection during AM by online monitoring of melt-pool features (e.g., temperature, geometry, and radiation intensity). 2226 Although these methods can examine porosity with a high accuracy, a large amount of iterative testing is required to establish a new relationship between the melt pool features and porosity once the target AM process or material is changed. In addition, the authors proposed a femtosecond laser-based transient thermoreflectance (TTR) measurement system for in situ porosity inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Metal additive manufacturing (AM) technology has emerged in the aircraft, automobile, and shipbuilding industries, and can realize designs that are not possible using conventional manufacturing methods 1 . Metal AM technologies can be classified into powder bed fusion (PBF) and direct energy deposition (DED) processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers were able to proscribe laser control techniques to mitigate keyhole formations [27] and a method to predict keyhole sizes based on laser intensity [26]. However, access to X-Ray imaging technology is still cost prohibitive for widespread commercial use and other research has focused around utilizing infrared, near infrared, photo diodes and optical cameras to analyze thermal information from the melt pool [33]- [47]. Researchers have shown that melt pool widths and lengths can be estimated [43]- [45] and abnormalities detected [37] directly by extracting and analyzing simple metrics and statistical measures.…”
Section: Introductionmentioning
confidence: 99%
“…Another research group was able to show that graph Fourier transform coefficients could be derived from two different photo diode sensors, and when these coefficients were used as input features for machine learning models, each model showed an improved accuracy in predicting porosity volume by layer compared to conventional metrics and statistical features [38]. Others have analyzed the aggregate thermal data of melt pools within a given layer and used Isolated Decision Trees [36] and Random Forest (RF) [47] models to detect anomalous melt pools and therefore predict porosities within that layer. Finally, a research group was able to utilize a pre-trained Convolutional Neural Networks (CNN) to predict whether a porosity existed at a location and its cross-sectional volume for a single-layer, single-track part, when optical images of the melt pool were input into the model in a frame-by-frame manner [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation